Callogorgia spp. and Their Brittle Stars: Recording Unknown Relationships in the Pacific Ocean and the Caribbean Sea - Mejía-Quintero, Katherine; Borrero-Pérez, Giomar H.; Montoya-Cadavid, Erika (Frontiers in Marine Science, 2021)
The habitat formed by Callogorgia species, with their abundance and colony sizes, provides an important refuge for a variety of brittle stars, which are recognized as octocoral’s epibiotic in shallow and deep environments. In these relationships, ophiurans benefit directly by being elevated, facilitating their feeding by suspension; however, the octocorals do not seem to benefit or be harmed. During three different projects developed in the Colombian Pacific (2012-2013) and Caribbean Sea (1998, 2012) by the Institute of Marine and Coastal Research (Invemar), different samplings were carried out on soft bottoms, through trawls with an epibenthic net. For the Pacific Ocean, 33 fragments of the octocoral Callogorgia cf. galapagensis Cairns, 2018 with 178 specimens of the ophiuroid Astrodia cf. excavata (Lütken and Mortensen, 1899) were found in two stations (530 and 668 m depth). Considering the abundance of A. cf excavata, other traits such as size, presence of mature gonads, and evidence of arm regeneration are detailed. In the Caribbean Sea, Callogorgia gracilis (Milne Edwards and Haime, 1857) was found with ophiuroids of the genera Asteroschema and Ophiomitra. The octocoral Callogorgia americana Cairns & Bayer, 2002 was also found, however without associate brittle stars. These findings constitute the first specific association reported in the Eastern Tropical Pacific and new relationships for the Caribbean Sea, reflecting a possible specific association between Callogorgia and Astrodia species that needs to be further explored. Callogorgia species and the brittlestar A. cf. excavata represent new records for the Colombian Pacific Ocean and the southern Caribbean Sea.